Síntese e caracterização preliminar de material fotossensível para manufatura aditiva - Souza, Giuliano Cesar Breda de (2014)
The use of manufacturing processes by adding layers of material, more specifically of additive manufacturing (AM), has been growing in recent years, strongly leveraged by technological innovations and making them an important ally in the product development process. Based on this trend, this work aims to present the proposal of a photosensitive resin synthesis for use in AM. Therefore, some syntheses composed of monomers, oligomers, photoinitiators and co-initiators, available in the national market, were developed and tested. The aim was to develop a Brazilian new acrylic resin, based in a photosensitive polymer compounds. Preliminary tests were performed to verify the minimum curing time of successive deposition layers on acrylic molds and exposed to radiation from UV-C with 250 nm of wavelength. Based on the curing times of each proposed synthesis, it was possible to determine a synthesis composed by 8,4% coinitiator, 46,2% monomers, 42% oligomer and 3,2% photoinitiatorto, to perform mechanical resistance test, bending tests, hardness tests Shore A and infrared spectrometry. Preliminary results were satisfactory, showing the possibility to use the resin in an AM process, for example, in material jetting based or vat photopolymerization based. It is possible to assert that, if applied, the resin will generate a defined geometry with application within the mechanical strength limits established by characterization performed.